Ubiquitin-Specific Peptidase 10 Protects Against Hepatic Ischaemic/Reperfusion Injury via TAK1 Signalling - Jiangqiao, Zhou; Tianyu, Wang; Zhongbao, Chen; Long, Zhang; Jilin, Zou; Xiaoxiong, Ma; Tao, Qiu (Frontiers in Immunology, 2020)
Ubiquitin-specific peptidase 10 (USP10) protein is a deubiquitination enzyme involved in many important biological processes. However, the function of USP10 in hepatic ischemic/reperfusion (I/R) injury remains unknown. The aim of this study was to explore the role of USP10 in hepatic I/R injury. USP10 Heterozygote mice and primary hepatocytes were used to construct hepatic I/R models. The effect of USP10 on hepatic I/R injury was examined via pathological and molecular analyses. Our results indicated that USP10 was significantly downregulated in the livers of mice after hepatic I/R injury and in hepatocytes subjected to hypoxia/reoxygenation stimulation. USP10 Heterozygote mice exhibited exacerbated hepatic I/R injury, as evidenced by enhanced liver inflammation via the NF-κB signalling pathway and increased hepatocyte apoptosis. Additionally, USP10 overexpression inhibited hepatocyte inﬂammation and apoptosis in hepatic I/R injury in vitro and in vivo. Mechanistically, our study demonstrated that USP10 knockdown exerted its detrimental effects on hepatic I/R injury by inducing activation of the transforming growth factor β-activated kinase 1 (TAK1)-JNK/p38 signalling pathways. TAK1 was required for USP10 function in hepatic I/R injury as TAK1 inhibition abolished USP10 function in vitro. In conclusion, our study demonstrated that USP10 plays a protective role in hepatic I/R injury by inhibiting the activation of the TAK1-JNK/p38 signalling pathways. Modulation of USP10/TAK1 might be a promising strategy to prevent this pathological process.